The Effect of Emotional Intelligence on Students' Islamic Education Learning Outcomes - Aprianda Aprianda (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
This research is motivated by the importance of student success in learning that is measured through learning outcomes. The reality shows that student learning outcomes in Islamic Education subjects are still low. Learning outcomes can be influenced by several factors, one of which is emotional intelligence. This study aims to determine the effect of emotional intelligence on student learning outcomes in Islamic Education subjects. This research is a quantitative approach by survey method. The population in this study was 40 students of the fifth grade at Sekolah Indonesia Johor Bahru, Malaysia. The total sampling technique selected that. The instrument in this research consisted of an emotional intelligence questionnaire and a learning outcome test. The data were analyzed using a simple linear regression test. Based on data analysis, it was found that emotional intelligence has a significant effect on student learning outcomes in Islamic Education subjects. Therefore, emotional intelligence needs to be honed from an early age because emotional intelligence is one of the axes of individual success in various aspects of life.